2021
DOI: 10.1152/ajprenal.00398.2020
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells cause renal and placental mitochondrial oxidative stress as mechanisms of hypertension in response to placental ischemia

Abstract: The Reduced Uterine Perfusion Pressure (RUPP) rat model and normal pregnant (NP) rat recipients of RUPP CD4+T cells recapitulate many characteristics of preeclampsia (PE) such as hypertension and oxidative stress. We have shown an important hypertensive role for NK cells to cause mitochondrial (mt) dysfunction in RUPP rats, however the role for RUPP CD4+ T cells to stimulate NK cells is unknown. Therefore, we hypothesize that RUPP induced CD4+ T cells activate NK cells to cause mt dysfunction/ROS as mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…This decrease in ATP and electron transport activity (ETC) reduces important cellular functions, leading to tissue damage and a change in organ homeostasis [ 20 ]. Our previous studies have demonstrated a role for mitochondrial dysfunction and oxidative stress in the kidney and placenta of the pregnant RUPP rat model of PE or in response to RUPP CD4+ T cells or TNF-α during pregnancy, indicating an important role for inflammation to mediate multi-organ mt ROS and dysfunction in association with hypertension in pregnant rats [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in ATP and electron transport activity (ETC) reduces important cellular functions, leading to tissue damage and a change in organ homeostasis [ 20 ]. Our previous studies have demonstrated a role for mitochondrial dysfunction and oxidative stress in the kidney and placenta of the pregnant RUPP rat model of PE or in response to RUPP CD4+ T cells or TNF-α during pregnancy, indicating an important role for inflammation to mediate multi-organ mt ROS and dysfunction in association with hypertension in pregnant rats [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, we demonstrated that the blockade of circulating AT1-AA from human PE sera was able to attenuate mtROS in HUVECS cultured with PE sera with and without AT1-AA blockade [23]. In addition to the AT1-AA, our lab has recently investigated the importance of mt oxidative stress in PE pathology, and has linked reduced vascular endothelial mt respiration and mtROS with the presence of CD4+ T cells stimulated in response to placental ischemia [23][24][25][26][27][28][29]. In a previous study from our groups, we showed that LD recombinant IL-2 improved T regs cell in RUPP rats.…”
Section: Discussionmentioning
confidence: 94%
“…Although this study investigated IL-2, there is still more to understand about preeclampsia and the other factors that contribute to this disease. In addition, multiple factors can induce placental mitochondrial ROS production, and for example, we have previously shown that natural killer cells [4] and CD4+ T cells [29] cause mitochondrial dysfunction in RUPP rats and endothelial cells incubated with RUPP serum exhibit mitochondrial ROS [6]. HUVECS treated with serum from PE women and incubated with MitoSOX Red indicated that serum from PE women contained circulating factors which contribute to mitochondrial dysfunction and an increase in mt ROS in cultured human vascular endothelial cells, thereby demonstrating that an increase in oxidative stress contributes to endothelial dysfunction [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy this results in mid-gestational differences in heart rate and mean arteriolar pressure, thus suggesting that these cell subsets may influence systemic vascular biology in the mother both developmentally and during pregnancy ( Burke et al, 2011 ). While evidence suggests that deficiency in a certain subset of T cells with regulatory properties (Treg) is associated with preeclampsia ( Cerdeira et al, 2012 ; Przybyl et al, 2015 ) our expanding knowledge of the complexity of these T cell subsets is likely to reveal associations between this disease and several members of the CD4 family of T cells ( Ahn et al, 2020 ; Saigusa et al, 2020 ; Deer et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%